Real-time diagnostic accuracy of blue light imaging, linked color imaging and white-light endoscopy for colorectal polyp characterization - Houwen, Britt B.S.L.; Vleugels, Jasper L.A.; Pellisé, Maria; Rivero-Sánchez, Liseth; Balaguer, Francesc; Bisschops, Raf; Tejpar, Sabine; Repici, Alessandro; Ramsoekh, D.; Jacobs, M. A.J.M; Schreuder, Ramon-Michel; Kamiński, Michal F.; Rupińska, Maria; Bhandari, Pradeep; van Oijen, M. G.H.; Koens, L.; Bastiaansen, Barbara A.J.; Tytgat, K. M.A.J.; Fockens, Paul; Dekker, Evelien; Hazewinkel, Yark (Endoscopy International Open, 2022)
Background and study aims Fujifilm has developed a novel ELUXEO 7000 endoscope system that employs light-emitting diodes (LEDs) at four different wavelengths as light sources that enable blue light imaging (BLI), linked color imaging (LCI), and high-definition white-light endoscopy (HD-WLE). The aim of this study was to address the diagnostic accuracy of real-time polyp characterization using BLI, LCI and HD-WLE (ELUXEO 7000 endoscopy system).Patients methods This is a prespecified post-hoc analysis of a prospective study in which 22 experienced endoscopists (> 2,000 colonoscopies) from eight international centers participated. Using a combination of BLI, LCI, and HD-WLE, lesions were endoscopically characterized including a high- or low-confidence statement. Per protocol, digital images were created from all three imaging modalities. Histopathology was the reference standard. Endoscopists were familiar with polyp characterization, but did not take dedicated training for purposes of this study.Results Overall, 341 lesions were detected in 332 patients. Of the lesions, 269 histologically confirmed polyps with an optical diagnosis were included for analysis (165 adenomas, 27 sessile serrated lesions, and 77 hyperplastic polyps). Overall, polyp characterization was performed with high confidence in 82.9 %. The overall accuracy for polyp characterization was 75.1 % (95 % confidence interval [CI] 69.5–80.1 %), compared with an accuracy of 78.0 % (95 % CI 72.0–83.2 %) for high confidence assignments. The accuracy for endoscopic characterization for diminutive polyps was 74.7 % (95 %CI 68.4–80.3 %), compared with an accuracy of 78.2 % (95 % CI 71.4–84.0 %) for high-confidence assignments.Conclusions The diagnostic accuracy of BLI, LCI, and HD-WLE by experienced endoscopist for real-time polyp characterization seems limited (NCT03344289).